Reading comprehension treatment in aphasia: a systematic review. Issue 6 (3rd June 2019) - Purdy, Mary; Coppens, Patrick; Madden, Elizabeth Brookshire; Mozeiko, Jennifer; Patterson, Janet; Wallace, Sarah E.; Freed, Donald
ABSTRACT: Background : Reading difficulties often present as a consequence of aphasia. The specific nature of reading deficits varies widely in manifestation, and the cause of these deficits may be the result of a phonological, lexical semantic, or cognitive impairment. Several treatments have been developed to address a range of impairments underlying reading difficulty. Aims : The purpose of this review is to describe the current research on reading comprehension treatments for persons with aphasia, assess the quality of the research, and summarize treatment outcomes. Methods & Procedures : A systematic review of the literature was conducted based on a set of a priori questions, inclusion/exclusion criteria, and pre-determined search parameters. Results were summarized according to treatment type, methodologic rigor, and outcomes. Outcomes & Results : Fifteen studies meeting criteria were identified. A variety of reading comprehension treatments was implemented including: oral reading, strategy-based, cognitive treatment, and hierarchical reading treatments. Quality ratings were highly variable, ranging from 3 to 9 (on a 12-point scale). Overall, 14 of the 18 individuals for whom individual data were provided demonstrated some degree of improvement (oral reading 4/5 participants, strategy based 4/6, and cognitive treatment 6/7). Gains were also evident for hierarchical reading treatment administered to participant groups via computer; however, the degree to which improvement reached statistical significance varied among studies. Conclusions : Reading comprehension treatments have the potential to improve reading comprehension ability in persons with aphasia; however, outcomes were variable within and among treatment methods. We suggest focusing future research on factors such as participant candidacy and treatment intensity using increased methodological rigor.